An analysis of data on Bunaji cattle at Birnin Kudu and Kabomo, northern Nigeria - Wheat, J.D.; Broadhurst, J. (1968)
Weights of Bunaji cattle at different ages at Kabomo and Birnin Kudu were analysed for differences caused by sire, sex and month of birth. At Kabomo where two sires represented were paternal half brothers, differences in weight due to sire effects were not significant at any age included in the study. At Birnin Kudu where the sires were less closely related to each other, beginning when the calves were six months of age, sire differences were significant at all older ages studied. Bulls were heavier than heifers at all ages, though at Kabomo the number of animals included was so small the differences were significant only at six months, but at Birnin Kudu differences attributed to sex were significant at all ages beginning at birth. Month of birth significantly affected weights of animals at Kabomo at six and twelve months of age. Birth weight, 12 weeks, 12 months, and 18 months weights were significantly affected by month of birth at Birnin Kudu. By the time the animals were two years old, month of birth no longer significantly affected weight. Cows at both stations averaged 42 months of age at first calving; average calving interval at Kabomo was 436 days, but at Birnin Kudu the average was only 388 days. Generation interval at Kabomo and Birnin Kudu were 72 and 75 months respectively, but average ages of the parents were more variable at Kabomo where the standard deviation was 27 months and at Birnin Kudu the standard deviation was only 12 months.